Simple Moving Average: Lebih baik dibanding Buy and Hold Strategy? - Jefarel Jefarel; Josephine Sudiman (The Indonesia Capital Market Institute, 2021)
The purpose of this study is to identify the optimal period of the Moving Average technique used to generate a better return towards 38 stocks included in the LQ 45 Index in Indonesia. The author uses 2 approaches, namely momentum and contrarian and applies the Simple Moving Average technique with various period modifications to daily trading data of 2018 and 2019. The optimal period is retested using data of 2020. The results suggest that the momentum strategy is superior to that of contrarian strategy, but overall these two strategies produce better returns than the Buy and Hold strategies. Specifically, the average loss of investors who adopt the Buy and Hold strategy is 26.43% in 2020, much higher than those who apply the contrarian strategy (the second approach) which will only experience a decrease in wealth value of 9.91% and 2.61% for those who implement momentum strategy (first approach).